1998
DOI: 10.1002/(sici)1096-8628(19981204)80:4<418::aid-ajmg22>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric dna break in a 10;16 reciprocal translocation associated with trisomy 16 confined placental mosaicism and maternal uniparental disomy for chromosome 16

Abstract: Stable centromeric breakage in non-acrocentric chromosomes and balanced reciprocal translocation mosaicism are both rare events. We studied a family in which the mother had mosaicism for a balanced reciprocal translocation between chromosomes 10 and 16 which was associated with a break in chromosome 16 centromere alpha-satellite DNA ¿146,XX,t(10;16)(q11.2;q11.1) [29]/46,XX[25]¿. The derivative chromosome 16 contained only a very small amount of 16 alpha-satellite DNA while the derivative 10 contained all of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Two of these (including one case that also showed true mosaicism) had abnormal phenotypes, whereas one was reported as normal at 21 weeks of gestation. Previously reported cases of UPD for chromosome 16 [Lindor et al, 1993;Kalousek et al, 1993;Sutcliffe et al, 1993;Vaughan et al, 1994;Whiteford et al, 1995;Schneider et al, 1996;Hsu et al, 1997;Robinson et al, 1997;Woo et al, 1997;Wang et al, 1997] as well as the three cases reported here indicate that intrauterine growth retardation is a frequent consequence but that a diversity of congenital anomalies may occur as well. An extensive review of prenatally detected trisomy 16 [Wolstenholme, 1995] indicates that maternal UPD 16 has been associated with pregnancy loss in the second or early third trimester as well as early delivery with severe growth retardation.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Two of these (including one case that also showed true mosaicism) had abnormal phenotypes, whereas one was reported as normal at 21 weeks of gestation. Previously reported cases of UPD for chromosome 16 [Lindor et al, 1993;Kalousek et al, 1993;Sutcliffe et al, 1993;Vaughan et al, 1994;Whiteford et al, 1995;Schneider et al, 1996;Hsu et al, 1997;Robinson et al, 1997;Woo et al, 1997;Wang et al, 1997] as well as the three cases reported here indicate that intrauterine growth retardation is a frequent consequence but that a diversity of congenital anomalies may occur as well. An extensive review of prenatally detected trisomy 16 [Wolstenholme, 1995] indicates that maternal UPD 16 has been associated with pregnancy loss in the second or early third trimester as well as early delivery with severe growth retardation.…”
Section: Discussionsupporting
confidence: 65%
“…Including this series, 33 cases of mosaic trisomy 16 detected through amniocentesis have been reported to date. Of 21 continuing pregnancies, 16 pregnancies (77%) had abnormal outcomes, including neonatal death [Watson et al, 1988;Devi et al, 1993], or liveborns with some combination of IUGR, CHD, and minor anomalies [Lindor et al, 1993;Pletcher et al, 1994;Paulyson et al, 1996;Devi et al, 1997;Hsu et al, 1997;Smith et al, 1997;Wang et al, 1997]. The remaining five pregnancies produced infants with an apparently normal phenotype at birth .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, so far, in three studies comprising 52 cases, no case of UPD was found [James et al, 1994; May et al, 1994; Miny et al, 1994]. In the literature, only five cases were reported; in three of them chromosome 15 was participating and UPD 15 was found [Smeets et al, 1992; Smith et al, 1994; Park et al, 1998], while chromosome 16 was in the remaining two [Dupont et al, 1998; Wang et al, 1998]. Four of these cases were found by a phenotype specific for one of the chromosomes involved [Smeets et al, 1992; Smith et al, 1994; Dupont et al, 1998; Park et al, 1998].…”
Section: Review and Meta‐analysismentioning
confidence: 99%